A Case of Inflammatory Generalized Type of Peeling Skin Syndrome Possibly Caused by a Homozygous Missense Mutation of CDSN - Hiroshi Kawakami; Masaki Uchiyama; Tatsuo Maeda; Takahiko Tsunoda; Yoshihiko Mitsuhashi; Ryoji Tsuboi (Case Reports in Dermatology, 2014)
A 54-year-old Japanese woman had repetitive superficial skin peeling and ensuing erythematous changes in the sites since infancy. Her parents had a consanguineous marriage, and she was the only individual affected in her family tree. The erythematous changes seemed to worsen in the summer. Histologically, hyperkeratosis and splitting of the epidermis within the stratum corneum was noted, and electron microscopy revealed shedding of corneal cells in the horny layer and normal-looking corneodesmosomes. Gene analysis revealed a homozygous missense mutation at c.1358G>A in CDSN. Electron microscopic examination of the length and number of corneodesmosomes revealed statistically significant shortness and sparsity in the affected individual (mean ± SD 386.2 ± 149.5 nm) compared with that of an age- and site-matched control (406.6 ± 182.3 nm). We speculate that this size shrinkage of corneodesmosomes might be the result of a missense mutation of CDSN and that this could be one of the factors contributing to the pathological process of skin peeling.